Oliver Wendell Holmes, Jr - White, G. Edward (Lives and legacies., 2006)
Known as the 'Great Dissenter, ' Oliver Wendell Holmes, Jr wrote some of the most eloquent opinions in the history of the United States Supreme Court. Holmes was responsible for some of the most important judicial opinions of the twentieth century. This biography offers readers a portrait of this singular individual.